Cytochrome c oxidase loses catalytic activity and structural integrity during the aging process in Drosophila melanogaster. - Ren, J.C.; Rebrin, I.; Klichko, V.; Orr, W.C.; Sohal, R.S. (Biochemical and Biophysical Research Communications, 2010)
The hypothesis, that structural deterioration of cytochrome c oxidase (CcO) is a causal factor in the age-related decline in mitochondrial respiratory activity and an increase in H?O? generation, was tested in Drosophila melanogaster. CcO activity and the levels of seven different nuclear DNA-encoded CcO subunits were determined at three different stages of adult life, namely, young-, middle-, and old-age. CcO activity declined progressively with age by 33%. Western blot analysis, using antibodies specific to Drosophila CcO subunits IV, Va, Vb, VIb, VIc, VIIc, and VIII, indicated that the abundance these polypeptides decreased, ranging from 11% to 40%, during aging. These and previous results suggest that CcO is a specific intra-mitochondrial site of age-related deterioration, which may have a broad impact on mitochondrial physiology.